Chemistry of essential oils of the shrub Lippia alba (Verbenaceae) from Mexico and Costa Rica (UNED Research Journal, 2022)
ABSTRACT: Introduction: Lippia is a Verbenaceous genus of flowering plants, which has about 200 species, distributed throughout the southern USA, Mexico, and Central America to South America. Objective: To study and compare the chemical compositions of the essential oils of L. alba growing in Mexico and Costa Rica. Methods: The essential oils were obtained by hydrodistillation in a Clevenger-type apparatus. The chemical composition of the oils was analyzed by capillary GC-FID and GC-MS using the retention indices on a DB-5 type capillary column in addition to mass spectral fragmentation patterns. Results: A total of 65 compounds were identified in the essential oil samples from both countries, accounting for 96,5-98,1% of the total amount of the oils. The main constituents of the Mexican sample were 1,8-cineole (22,3%), myrcenone (11,2%), myrcene (10,9%), (E)-ocimenone (10,7%), (Z)-ocimenone (7,5%), and sabinene (6,8%), while for essential oil from Costa Rica the major compounds were myrcenone (30,4%), 1,8-cineole (21,4%), myrcene (11,0%), hedycaryol (4,4%), and sabinene (4,3%). Samples from both countries can be classified as belonging to chemotype “tagetenone”. Lippia alba (strong form) from Costa Rica produces essential oil that differs from all other essential oils of L. alba studied to date because it contained the sesquiterpenoids hedycaryol and the isomeric alcohols α-eudesmol, β-eudesmol, and γ-eudesmol. Conclusion: L. alba (strong form) from Costa Rica can be classified as a new subtype of the chemotype “tagetenone” (chemotype II).